1984
DOI: 10.1104/pp.76.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on myo-Inositol-1-phosphatase from the Pollen of Lilium longiflorum Thunb

Abstract: myo-Inositol-l-phosphatase has been purified to homogeneity from Lilium longiflorum pollen using an alternative procedure which includes pH change and phenyl Sepharose column chromatography. Sodium dodecyl sulfate-polyacrylamide gel electrophoretic analysis shows that the enzyme is a dimer (subunit molecular weight, 29,000 daltons). The enzyme is stable at low pH values and is inactivated only below pH 3.0. In addition to IL-and ID-myo-inositol-l-phosphate, it shows high specificity for IL-chiro-inositol-3-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…In addition, Fru 1-P, Fru 1,6-bisP, Glc 6-P, D-a-glycerophosphate, sorbitol 6-P, and myoinositol 2-P are not good substrates for VTC4, as seen by little to no hydrolysis in assays (Table I). Together, these data indicate that VTC4 is a somewhat promiscuous enzyme and that the C1 phosphate position in a six-member ring substrate is important for catalysis, as was noted previously by others (Gumber et al, 1984;Laing et al, 2004;Islas-Flores and Villanueva, 2007). In contrast to what has been reported previously (Laing et al, 2004), we conclude that VTC4 has a minor (1.6-to 2.4-fold) difference in substrate hydrolysis of L-Gal 1-P as compared with D-Ins 3-P or D-Ins 1-P. We also note the difference between VTC4 and human IMP regarding D-Gal 1-P.…”
Section: Expression Of Recombinant Atvtc4 Proteinsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, Fru 1-P, Fru 1,6-bisP, Glc 6-P, D-a-glycerophosphate, sorbitol 6-P, and myoinositol 2-P are not good substrates for VTC4, as seen by little to no hydrolysis in assays (Table I). Together, these data indicate that VTC4 is a somewhat promiscuous enzyme and that the C1 phosphate position in a six-member ring substrate is important for catalysis, as was noted previously by others (Gumber et al, 1984;Laing et al, 2004;Islas-Flores and Villanueva, 2007). In contrast to what has been reported previously (Laing et al, 2004), we conclude that VTC4 has a minor (1.6-to 2.4-fold) difference in substrate hydrolysis of L-Gal 1-P as compared with D-Ins 3-P or D-Ins 1-P. We also note the difference between VTC4 and human IMP regarding D-Gal 1-P.…”
Section: Expression Of Recombinant Atvtc4 Proteinsupporting
confidence: 54%
“…It has been reported that Mg 2+ is necessary for maximal activity of IMP and that a pH of 7.5 is optimal (Gumber et al, 1984;Laing et al, 2004;Islas-Flores and Villanueva, 2007). Selected concentrations from 0 to 50 mM MgCl 2 were added to reactions with D-Ins 3-P to determine the optimum MgCl 2 for enzyme activity (Fig.…”
Section: Expression Of Recombinant Atvtc4 Proteinmentioning
confidence: 99%
“…With respect to Li +, no effect on InsP3 degradation was observed, but InsP2 dephosphorylation was inhibited at high concentrations [68]. The Li ÷ results are consistent with those of an inositol-1-phosphatase from pollen purified to homogeneity [35].…”
Section: Hydrolysis Of Inositol Phosphatessupporting
confidence: 77%
“…In the myo-inositol pathway, inositol-1-P is derived from glucose-6-P. It is then converted to myo-inositol by a phosphatase (19)(20)(21) and, thence, to glucuronic acid by inositol oxygenase.…”
mentioning
confidence: 99%